Pemerolehan Bahasa pada Anak Penyandang "Down Syndrome" - Muldawati*, Muldawati; Rosidin, Odien; Juansah, Dase Erwin (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2024)
This article analyzes, classifies and explains the acquisition of speech in children with Down syndrome, both reduction and substitution. Qualitative descriptive research method, data collection techniques: listening, taking notes, interviews and documentation. The results of speech reduction research for people with Down syndrome experienced difficulties with vowels [e] and vowels [i]. Consonant difficulties include the bilabial consonant phoneme [b] [m] [p], the alveolar consonant phoneme [l] [r] [n] [s], the glottal consonant phoneme [h], and the dental consonant phoneme [t]. Meanwhile, in speech substitution, 15 phonemes are substituted, namely [l] ? [y], [l] ? [r], [j] ? [s], [d] ? [i], [k] ? [ t], [g] ? [h], [s] ? [w], [b] ? [w], [b] ? [y], [r] ? [y], [t] ? [w] , [t] ? [?], [?] ? [g], [n] ? [?], [?] ? [n].Keywords: down syndrome; psycholinguistics; speechAbstrak:Artikel ini menganalisis, mengklasifikasikan, menjelaskan pemerolehan ujaran pada anak down syndrome baik reduksi maupun substitusinya. Metode penelitian deskriptif kualitatif, teknik pengumpulan data simak, catat, wawancara, dan dokumentasi. Hasil penelitian reduksi ujaran penyandang down syndrome mengalami kesulitan vokal [e] dan vokal [i]. Kesulitan konsonan yaitu fonem konsonan bilabial [b] [m] [p], fonem konsonan alveolar [l] [r] [n] [s], fonem konsonan glotal [h], dan fonem konsonan dental [t]. Sedangkan pada substitusi ujaran  fonem yang mengalami substitusi sebanyak 15 fonem, yaitu [l] ? [y], [l] ? [r], [j] ? [s], [d] ? [i], [k] ? [t], [g] ? [h], [s] ? [w], [b] ? [w], [b] ? [y], [r] ? [y], [t] ? [w], [t] ? [?], [?] ? [g], [n] ? [?], [?] ? [n].Kata kunci: down syndrome; psikolinguistik; ujaran